2017
DOI: 10.9767/bcrec.12.3.900.437-451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Conditions on the Catalytic Activity of CuMnOx Catalysts for CO Oxidation

Abstract: The hopcalite (CuMnOx) catalyst is a well-known catalyst for oxidation of CO at ambient temperature. It has prepared by co-precipitation method and the preparation parameters were like Copper/Manganese (Cu:Mn) molar ratios, drying temperature, drying time, calcination temperature and calcination time has an influence on activity of the resultant catalyst. The activity of the catalyst was measured in flowing air calcinations (FAC) conditions. The reaction temperature was increased from ambient to a higher value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In view of this, a minor modification in the calcination process causes a notable improvement in the physicochemical properties of the catalyst. Therefore, we believe that the reduction in calcination time could affect the catalyst properties, which eventually affects their catalytic activity [21]. In the following, the calcination time is changed to 1 h, 3 h, and 5 h for the MPdA catalyst at 600 • C, which was found to yield the best results among the different calcination temperatures tested for H 12 -MBP dehydrogenation.…”
Section: Influence Of Calcination Timementioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, a minor modification in the calcination process causes a notable improvement in the physicochemical properties of the catalyst. Therefore, we believe that the reduction in calcination time could affect the catalyst properties, which eventually affects their catalytic activity [21]. In the following, the calcination time is changed to 1 h, 3 h, and 5 h for the MPdA catalyst at 600 • C, which was found to yield the best results among the different calcination temperatures tested for H 12 -MBP dehydrogenation.…”
Section: Influence Of Calcination Timementioning
confidence: 99%
“…The unique properties of the MPdA catalyst were shaped by the commencement of a solvent deficient environment in the synthesis, which not only limits the nucleation and growth of nanoparticles, but also introduces the Pd and Al species into the assembly of the mesopore wall. Therefore, the above results encouraged us to further examine the MPdA catalyst by changing the calcination conditions such as temperature and time, which are known to be effective in regulating the physicochemical properties with regard to their dehydrogenation proficiencies [20,21]. Hence, the present work focuses on the investigation of the sensitivity and effectiveness of the SDP method by varying the calcination temperature and calcination time.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of manganese oxide is likely to facilitate the reduction of copper oxide, involving coordination between CuO and MnO 2 , the manganese oxide acting as an oxygen donor and copper oxide acting as the oxygen acceptor. A previous work demonstrated that the presence of Cu 2+ and Mn 3+ is essential for the high catalytic activity of CuMnOx catalyst [33,34]. In present study, the different types of precursors have been used to change the crystalline phase of the catalysts and to find out the best CuMnOx catalyst, which will give the highest activity for CO oxidation.…”
Section: Introductionmentioning
confidence: 95%
“…The metal-support interaction may alter the catalyst properties due to its strong or low interaction. The metal-support interaction is strongly depend on few factors, such as catalyst preparation method, thermal treatment (calcination, reduction, or drying), and metal content in the catalyst [16][17][18].…”
Section: Introductionmentioning
confidence: 99%